Evaluation and application of a next generation sequencing approach for meat species identification. (April 2020) - Cottenet, Geoffrey; Blancpain, Carine; Chuah, Poh Fong; Cavin, Christophe
Abstract: Food fraud and species substitution are topical issues that must be addressed for quality and safety purposes and to maintain consumers' trust. DNA-based methods are considered as the reference approach for species identification, but they are usually limited to a few species only. In this study, the performance of a commercial NGS solution has been evaluated as an untargeted tool to identify meat species. Tested on pure meat samples, all species were correctly identified including several exotic species, and close-related species were correctly differentiated. Species were successfully detected and identified in mixtures down to 1% (w/w). The reliability of the tool was further confirmed on several proficiency test samples, and promising quantification data were obtained. Finally, 45 ground meat samples sourced from local European and Asian markets were analyzed and 18% of them showed cases of adulteration with undeclared meat species. Highlights: Untargeted meat species identification. 1% adulterated level with foreign species detected. Satisfactory results on proficiency test samples. Promising quantification data obtained. Amongst 45 ground meat samples analyzed, 18% contained undeclared species.